Effect of varying rates of nitrogen and its schedule of split application in baby corn (Zea mays) - THAKUR, D R; SHARMA, VINOD (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was carried out during rainy seasons (kharif) of 1995 and 1996 in the mid-hill sub-humid agroclimateof north-western Himalayan region at Bajaura to work out the nitrogen requirement and its schedule of splitapplication in baby Com (Zea mays). Baby com yield (1 450 kg/ha) increased significantly up to 150 kg N/ha application,whereas cob yield with husk and fodder yield registered significant increase up to 200 kg N/ha. Nitrogen applied in3 equal splits (each at sowing, 25 and 40 days atrer sowing) gave sigllificantiy highest baby corn yield (l5I7 kg/ha).Highest net return (Rs 48 481/ha) and net return/rupee invested (Rs 1.44) were obtained with 200 kg N/ha applied in 3equal splits.